HILIRISASI CPO DAN IMPLIKASINYA TERHADAP TRANSFORMASI EKONOMI PROVINSI RIAU - Muhamad Nur Ziqrullah; Kenepri Kenepri; Amri Hakim (Jurnal Cakrawala Ilmiah, 2026)
This study analyzes the impact of Crude Palm Oil (CPO) downstreaming policy on economic transformation in Riau Province using a mixed methods approach (concurrent triangulation design). Quantitative data were collected from 100 stakeholders via structured questionnaires, while qualitative data were gathered through in-depth interviews and document analysis. Three advanced analytical techniques were employed: Descriptive Statistics, the Leontief Interregional Input-Output (IRIO) Model, and Structural Equation Modeling (SEM) via SmartPLS. Results show the downstreaming policy scored very high (mean = 4.22), with an output multiplier of 2.35. SEM confirmed a positive and significant total effect on economic transformation (β = 0.79; R² = 0.71), partially mediated by industrial value-added. CPO downstream industry was confirmed as a key sector with forward linkage 1.68 and backward linkage 1.42. This study concludes that CPO downstreaming has shifted Riau's economy toward manufacturing, though infrastructure and smallholder partnerships require further optimization.